풍향과 동 배치에 따른 아파트 단지의 풍압계수 및 자연환기성능 비교 연구 - 최재솔(Choi Jae-Sol); 김의종(Kim Eui-Jong); 윤성훈(Yoon Seong-Hoon) (한국태양에너지학회 논문집, 2021)
This study aimed to provide basic data and serve as a reference for the planning of natural ventilation in apartment complexes. To analyze the characteristics of the wind pressure coefficients and natural ventilation performance, six cases were selected. The cases were differentiated according to the building layout and height, and CFD (Computational Fluid Dynamics) analysis was conducted under three wind conditions. The results of natural ventilation performance based on wind pressure coefficients showed that a two-line layout provided better ventilation performance than a four-line layout under the same conditions. From the above results, the wind pressure coefficients and ventilation performance can be roughly categorized according to the building arrangement. KCI Citation Count: 0